The concept and methods of knowledge form islamic epistemological perspective - Rahimah, Embong; Nadhirah, Nordin; Abdul Hakim, Abdullah; Syed Hadzrullathfi, Syed Omar; Fadzli, Adam; Nor Afizan, Che Omar; Siti Fatimah, Mohd (2016)
The paper aims to examine the nature of knowledge from Islamic epistemological perspective. It highlights the significance of thinking as illuminated in various Quranic messages which are alluring to the use of reason. The ultimate source of all knowledge is the God. the best teacher for mankind who has granted two references, namely Divine revelation (al-wahy) and the law of nature (al-kawn). Islam considers both references as equally important for human progress. Thus, it explores two major methods of obtaining knowledge namely contemplation (tadabbur) and thinking (tafakkur). The former is a method of studying readable signs of God (Ayat Allah al-Maqruah) meanwhile the latter is a scientific method of investigating visible signs of God (Ayat Allah al-Manzurah). This leads to identifying the levels of human perceptual faculties which are basic instinct, five physical senses, intellect and intuition, and the highest level is the Divine revelation. This study also found that Islamic epistemology denies division between knowledge of Supreme Being and that of physical world and promotes the unity between them. This resulted in the application of unification (Tawhidic) principle to all domains of human intellectual faculties and educational activities. This study gives some implications on the unity, enumeration and hierarchy of Knowledge. It is suggested that an integrated curriculum and a holistic education should be derived from the Islamic